Intralesional Bleomycin in Periungual Warts: A Prospective Randomised Controlled Study - Kallolinee Samal; Nibedita Dixit; Srigopal Mohanty; Debjit Kar; Siddhartha Dash; Manoj Kumar Nayak (Journal of Clinical and Diagnostic Research)
Introduction: Periungual Warts (PW) are difficult to treat because of their challenging location, high recurrence rate and resistance to treatment. Bleomycin is a cheaper and readily available drug that has potential efficacy in treating warts, although limited data on its use are available in the literature. Aim: To study the efficacy and safety of Intralesional (IL) bleomycin in treating PW. Materials and Methods: A prospective randomised controlled study was conducted at the Department of Dermatology, SCB Medical College and Hospital, Odisha, India, from September 2019 to August 2020. A total of 56 patients with PW were randomised equally by block randomisation into two groups: Group A and Group B. Group A received 1 U/mL IL bleomycin, while Group B was given dH2O. Follow-up assessments were conducted at four, twelve and 24-week intervals. All follow-up visits included photographic documentation to confirm the cure rates before and after treatment. To evaluate the treatment’s safety and effectiveness, the number and size of wart lesions, as well as injection side-effects, were noted at baseline and during each follow-up visit. Data analysis was performed using Statistical Package for Social Sciences (SPSS) version 26.0 (SPSS Inc., Chicago, IL). The Chi-square test was used to compare the study and control groups and to conduct follow-up analysis. Statistical significance was set at a level of ≤0.05, with a confidence interval of 95%. Results: Group A and B patients had 54 and 42 wart lesions, respectively. The complete cure rate in Groups A and B was 74.1% (40/54 warts) and 4.8% (2/42 warts), respectively, after four weeks. After the second follow-up, at twelve weeks, the cure rate was significantly higher in the experimental group: 97.3% versus 4.76% (p=0.00001). All cases during the IL injection experienced pain at the injection site and haemorrhagic eschar was observed in every case within the first week of the IL injection. No significant systemic adverse effects were noted. Conclusion: Intralesional bleomycin is highly efficacious and safe for the treatment of warts. Systemic side-effects are negligible, making it an effective treatment option for clearing warts in difficult areas, such as PW.